Inside Cover: Immobilization of two (R)‐Amine Transaminases on an Optimized Chitosan Support for the Enzymatic Synthesis of Optically Pure Amines (ChemCatChem 2/2013). Issue 2 (30th January 2013) - Mallin, Hendrik; Menyes, Ulf; Vorhaben, Torge; Höhne, Matthias; Bornscheuer, Uwe T.
<x xml:space="preserve">Abstract</x> The crab shell catalysts! The cover picture shows a porous structure of chitosan in different magnifications and the reaction scheme for the highly enantioselective amination of 2‐hexanone using amine transaminases covalently immobilized on this carrier material, which was obtained from chitin. In their Full Paper on p. 588 ff., U. T. Bornscheuer et al. describe the modification of the chitosan support, the covalent immobilization of three enzymes, and their application in an asymmetric synthesis.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>